2010
DOI: 10.5194/cpd-6-2455-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The global ocean circulation on a retrograde rotating earth

Abstract: To understand the three-dimensional ocean circulation patterns that have occurred in past continental geometries, it is crucial to study the role of the present-day continental geometry and surface (wind stress and buoyancy) forcing on the present-day global ocean circulation. This circulation, often referred to as the Conveyor state, is characterized by an Atlantic Meridional Overturning Circulation (MOC) with deep water formation at northern latitudes and the absence of such deep water formation in the North… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The direction of the simulated changes is similar to the outcome of experiments by Smith et al (2008) and Kamphuis et al (2011), but in general the circulation changes found in our model are more similar to the results of Smith et al (2008) than to the results of Kamphuis et al (2011). Both studies showed a weakening of the Atlantic MOC together with a surface freshening in the North Atlantic and saltier surface conditions in the North Pacific.…”
Section: Ocean Physicssupporting
confidence: 89%
See 4 more Smart Citations
“…The direction of the simulated changes is similar to the outcome of experiments by Smith et al (2008) and Kamphuis et al (2011), but in general the circulation changes found in our model are more similar to the results of Smith et al (2008) than to the results of Kamphuis et al (2011). Both studies showed a weakening of the Atlantic MOC together with a surface freshening in the North Atlantic and saltier surface conditions in the North Pacific.…”
Section: Ocean Physicssupporting
confidence: 89%
“…An important and outstanding question of physical oceanography is why the North Atlantic is so disproportionate in its production of deep water, with very little or no deep water formed in the North Pacific. Kamphuis et al (2011) suggested that the more southward continental boundary of the Pacific limits deep water formation as compared to the Atlantic, which extends well into the Arctic. Other studies (e.g., Warren, 1983) have suggested that the freshening of the Pacific relative to the Atlantic stabilizes the overturning pattern.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations